Pengaruh Rasio Likuiditas, Struktur Modal, dan Good Corporate Governance terhadap Profitabilitas - Maya Permata Sari; Syaiful Bahri; Nurdiana Fitri Isnaini (CV. Kalimasada Group, 2025)
This study analyzes the impact of liquidity, capital structure, and good corporate governance (GCG) on profitability (return on assets) in food and beverage companies listed on the Indonesia Stock Exchange for the 2020-2024 period. This study aims to provide an empirical overview of internal company factors that influence the financial performance of the food and beverage sector in Indonesia. This research plays a significant role because this sector is one of the strategic areas that demonstrates good resilience to the economy. Therefore, it is hoped that the results of this study can contribute to management in making financial and management decisions. Furthermore, this study aims to develop the literature that examines the impact of good corporate governance on profitability, focusing on the variables of the board of directors, the board of commissioners, and the audit committee as benchmarks for GCG. The sample consisted of 22 companies covering 110 observations. The method applied in this analysis was multiple linear regression. The results of the study indicate that liquidity does not significantly affect ROA, while capital structure and board direction have a significant influence. However, the board of commissioners and the audit committee do not significantly contribute to profitability